Superabsorbent Fabric Based on Weft‐Back Weave Structure for Efficient Evaporative Cooling. Issue 1 (10th November 2020) - Li, Xiaoyan; Javed, Muhammad; Guo, Yang; Luo, Ming; Cai, Zaisheng; Xu, Bi
Abstract: Fabrics with efficient evaporative cooling performance not only improve personal thermal comfort but also show essential significance in energy‐saving. This study reports an integrated cooling fabric based on the weft‐back weave structure. By adjusting the type of warp and weft yarns, water absorbency and wettability of the fabric can be altered to achieve the regulation of the fabric's performance. The prepared single‐sided superabsorbent cooling fabric (S‐SAF) shows a water absorbency of 370% and a water retention time of 90 min. S‐SAF can efficiently reduce the indoor temperature of a simulated building by about 6 °C under the radiation of 200 W m −2, and the cooling time is extended up to 150 min. Meanwhile, S‐SAF shows excellent evaporative cooling for the human body and exhibits good recyclability. Therefore, the prepared cooling fabric achieves thermal comfort under a hot and dry environment and has broad application prospects in person and building cooling. Abstract : A weft‐back structured evaporative cooling fabric is weaved by integrating superabsorbent yarns with water‐resistant hollow polyester yarns. The prepared fabric shows a high water absorbency and a long water retention time, which leads to a long‐lasting evaporative cooling effect. This cooling fabric achieves thermal comfort under a hot and dry environment and has broad application prospects in cooling person and buildings.